2011
DOI: 10.1016/j.iimb.2010.12.002
|View full text |Cite
|
Sign up to set email alerts
|

The digital divide in rural South Asia: Survey evidence from Bangladesh, Nepal and Sri Lanka

Abstract: This paper examines bridging the digital divide through organisational innovations that provide low cost Internet access in developing countries, within the existing conditions of income levels. We use survey data from three South Asian countries, Bangladesh, Nepal and Sri Lanka, to examine factors influencing patterns of computer and Internet use. We find that education plays a key role, in terms of its acquisition as a reason for computer and Internet use, and as an enabling variable (especially in the case … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
21
0
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(22 citation statements)
references
References 17 publications
0
21
0
1
Order By: Relevance
“…Moreover, 29 out of the 35 included studies deployed an online approach for recruiting study participants and collecting data. Moreover, South Asian countries have a profound digital divide [ 89 , 90 ]; therefore, people who do not use digital devices or services may not be able to participate in surveys that are administered through internet. Furthermore, rural and marginalized communities may have limited access to digital resources that may systematically exclude them from online participation [ 91 ].…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, 29 out of the 35 included studies deployed an online approach for recruiting study participants and collecting data. Moreover, South Asian countries have a profound digital divide [ 89 , 90 ]; therefore, people who do not use digital devices or services may not be able to participate in surveys that are administered through internet. Furthermore, rural and marginalized communities may have limited access to digital resources that may systematically exclude them from online participation [ 91 ].…”
Section: Discussionmentioning
confidence: 99%
“…The literature on mobile phone adoption also identified income as a significant influencing factor (Quibria et al, 2003;Barrantes and Galperin, 2008;Zhou et al, 2011;Zanello, 2012;Deen-Swarray, 2016). Using a USA case study, Rice and Katz (2003) argued that there was not only an Internet digital divide but there was also a mobile phone digital divide.…”
Section: Determinants Of Ict Adoptionmentioning
confidence: 99%
“…Some scholars have argued that the digital divide is not a technological problem but a social problem and the consequence of underlying social inequalities (Barrantes and Galperin, 2008;Fuchs, 2009). Evidence from South Asian countries, including Bangladesh, Nepal, Pakistan and Sri Lanka, also suggests income is a significant influence in computer and Internet adoption (Zhou et al, 2011;Rehan and Ali, 2014). The same authors also identified education and access to one's own telephone as significant factors for computer and Internet adoption.…”
Section: Determinants Of Ict Adoptionmentioning
confidence: 99%
“…Nowadays, most children from developed world can easily get the access to the computer [4]. However, not all children from all comers of the world are fortunate to get the access to computer technology.…”
Section: A Computers In Educationmentioning
confidence: 99%